2023
DOI: 10.1186/s12951-023-01954-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-125b-5p derived from adipose-derived mesenchymal stem cells enhance diabetic hindlimb ischemia repair via targeting alkaline ceramidase 2

Abstract: Introduction Ischemic diseases caused by diabetes continue to pose a major health challenge and effective treatments are in high demand. Mesenchymal stem cells (MSCs) derived exosomes have aroused broad attention as a cell-free treatment for ischemic diseases. However, the efficacy of exosomes from adipose-derived mesenchymal stem cells (ADSC-Exos) in treating diabetic lower limb ischemic injury remains unclear. Methods Exosomes were isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The exosome-rich medium can then be harvested and centrifuged to remove residual cells and debris. An ultracentrifugation process helps pellet the exosomes, which are resuspended and further refined using techniques like size-exclusion chromatography, ensuring a high-quality exosome yield [ 76 , 78 , 79 ], as illustrated in Figure 2 .…”
Section: Sources Of Stem Cell-derived Exosomes: Molecular Traits Func...mentioning
confidence: 99%
See 3 more Smart Citations
“…The exosome-rich medium can then be harvested and centrifuged to remove residual cells and debris. An ultracentrifugation process helps pellet the exosomes, which are resuspended and further refined using techniques like size-exclusion chromatography, ensuring a high-quality exosome yield [ 76 , 78 , 79 ], as illustrated in Figure 2 .…”
Section: Sources Of Stem Cell-derived Exosomes: Molecular Traits Func...mentioning
confidence: 99%
“…They exhibit a distinctive cup-like shape when viewed under transmission electron microscopy (TEM). Research focusing on these exosomes in the context of lower limb ischemia identified the presence of exosomal markers CD9, CD63, and CD81, while markers GM130 and β-tubulin were found to be absent [ 78 , 79 ]. Interestingly, a recent study has highlighted the role of the microRNA miR-125b-5p, found in ADSC-exos, in repairing muscle tissue damaged by ischemia.…”
Section: Sources Of Stem Cell-derived Exosomes: Molecular Traits Func...mentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes (Exos), small vesicles with 50–150 nm diameters, play a crucial role in regulating cell-to-cell communication by transferring proteins, lipids, DNA, RNA, and other bioactive substances [ 17 , 18 ]. Various studies have demonstrated the potential of stem cell-derived exosomes in promoting wound repair through different mechanisms, such as down-regulating transforming growth factor (TGF-β) expression, activating the AKT/eNOS pathway for angiogenesis, and enhancing cell function while inhibiting apoptosis [ [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%